GAMBARAN KEPERCAYAAN DIRI SISWA SMK ALOER WARGAKUSUMAH - Silmi Mutaharoh; Heris Hendriana; Ecep Supriatna (IKIP Siliwangi, 2023)
Self Confidence is something that is need by an individual. This study aims to describe the confidence profil of the Aloer Wargakusumah Vocational High School students. The method used in this research is descriptive quantitative, with the number of subjects as many as 102 students of class XI SMK Aloer Wargakusumah. The results showed that the level of self confidence was high at 15%, low at 71% and moderate at 13%, which had aspects of self confidace that were 80% confident in their abilities 83%, optimisic 86%, responsible, 76%, rasional and realistic 72%. Meanwhile, based on gender the cnnfidence level of women is higher than that of me, in the female gendeer self confidence dominates with a value of 55% an menas much as 45%. Thus SMK Aloer wargaksumah student generally have moderate. Keywords: Self confidence, Students